(untitled) (Academia Journal of Medicine, 2025)
Diabetic retinopathy (DR) is one of the most common microvascular complications of diabetes mellitus and a leading cause of preventable blindness globally. Despite advancements in modern ophthalmology, current treatment options are often invasive and expensive, leading to an increased interest in complementary and alternative therapies, especially Ayurveda. This review explores the pathophysiology, progression, and classification of diabetic retinopathy and evaluates the potential of Ayurvedic palliative therapies and interventions. We review classical Ayurvedic texts, recent clinical studies, and experimental data to understand the efficacy of herbs, Panchakarma, and Rasayana therapy in DR management. This integrated approach may offer a holistic and cost-effective solution, improving the quality of life for diabetic patients.